(untitled) (Prassi Ecdotiche della Modernità Letteraria, 2021)
The essay analyses the relationship between the first and the second edition of the Canzone and the Sophonisba by G. G. Trissino, studying the adjustments made by the author in few months and finding out similar corrections in each of the two works. Moreover, it demonstrates that many of these variants are to be connected with the publication of the Ɛpistola de le lettere and its linguistic proposals.